Global, regional, and national burden of type 2 diabetes mellitus caused by high BMI from 1990 to 2021, and forecasts to 2045: analysis from the global burden of disease study 2021 - Huang, Xin; Wu, Yanyan; Ni, Yulu; Xu, Haiyan; He, Yinhui (Frontiers in Public Health, 2025)
ObjectiveTo produce estimates of the global burden of type 2 diabetes mellitus (T2DM) caused by high body mass index (high BMI) and its impact for 2021 and projections for 2045.MethodsWe downloaded data from the Global Burden of Disease Study 2021(GBD 2021) to estimate the disease burden of T2DM caused by high BMI. Secondary analyses were performed by year, age, gender, region, and socio-demographic index (SDI).ResultsGlobally, the all-ages number of T2DM-related deaths has increased significantly from 238.1 thousand to 723.7 thousand, representing a 203.9% increase since 1990. And the all-ages number of T2DM-raleted DALYs has raised from 10.4 million to 39.3 million, increased by 276.7% from 1990. The burden was expected to continue to increase to 1296.7 thousand by 2045 for all-ages number of deaths, and 85.5 million by 2045 for all-ages number of DALYs. The curves of T2DM-related burden showed an intersection for different genders around the age of 60, beyond which women exhibit a higher burden, compared to men. The disease burden of T2DM caused by high BMI shows a significant upward trend across all SDI groups, with a heavier burden on women, especially in the postmenopausal female population. In 2021, among the 204 countries and territories, the top 3 largest number of T2DM-related burden caused by high BMI occurred in China, India, and United States. The top three countries with highest T2DM-related rate caused by high BMI were Fiji, Marshall Islands, and Kiribati.ConclusionOur study reveals that the disease burden of T2DM caused by high BMI is significantly increasing and is expected to continue rising in the future. Women bear a heavier burden, particularly postmenopausal women, and there are significant differences in the disease burden across different geographical regions, and socioeconomic statuses. Targeted considerations and specific strategies are essential to address these disparities, thereby improving public health and reducing the burden.